2016
DOI: 10.1007/s10620-016-4341-9
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features and Predisposing Factors of Asymptomatic Erosive Esophagitis

Abstract: KCT0001716.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Gastroesophageal reflux disease (GERD) is increasing, affecting up to 17% of the population in Asian countries and up to 40% in Western countries . The condition becomes apparent when contents of the gastric juice, specifically pepsin, leave the stomach and backflow into the esophagus, often causing damage and a myriad of symptoms including heartburn .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastroesophageal reflux disease (GERD) is increasing, affecting up to 17% of the population in Asian countries and up to 40% in Western countries . The condition becomes apparent when contents of the gastric juice, specifically pepsin, leave the stomach and backflow into the esophagus, often causing damage and a myriad of symptoms including heartburn .…”
Section: Introductionmentioning
confidence: 99%
“…EE affects only 30% of the GERD population but it is extremely serious. This subcategory causes damage and may lead to additional future complications including Barrett's esophagus and adenocarcinoma . Affecting up to 70% of patients with GERD, NERD is the most frequent form of reflux disease .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study that was conducted in subjects attending health examinations in Taiwan reported that male sex and hiatus hernias were positive risk factors for silent GERD, while the active infection of H. pylori was negatively associated with the occurrence of silent GERD [ 7 ]. Male sex, a BMI over 25, smoking, and/or drinking were also reported to be positive or negative factors for the occurrence of asymptomatic esophagitis in other studies done in Korea [ 11 ].…”
Section: Discussionmentioning
confidence: 94%
“…It is common to observe silent GERD and hypertension concurrently, since many risk factors are shared by these two diseases. Risk factors including age, obesity, male sex, smoking, alcohol consumption, and education level have been reported to be significantly associated with both silent GERD and hypertension [ 11 17 ]. More importantly, previous studies have shown that silent GERD and hypertension not only coexist but they also mutually reinforce each other.…”
Section: Introductionmentioning
confidence: 99%
“…По этиологическому признаку выделяются эзофагиты [1]: ■ Поражения при ГЭРБ (наиболее частая причина). ■ Инфекционные -вирусные, грибковые, бактериальные.…”
unclassified